The Ancient Egyptian Book of the Moon - Priskin, Gyula (Archaeopress Egyptology Ser., 2019)
This book proposes that Coffin Texts spells 154-160, recorded at beginning of the 2nd millennium BCE, form the oldest composition about the moon in ancient Egypt and, indeed, the world. The detailed analysis of these spells, based on a new translation, reveals that they provide a chronologically ordered account of the phenomena of a lunar month.